KAJIAN MUSIKAL KOMPOSISI GAMELAN LOGDRO BANGSAKU KARYA BLACIUS SUBONO - Wibi Endah Pambudi; Purwa Askanta; Guruh Purbo Pramono (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2024)
The jurnal entitled “The Study of Musical Composition of Gamelan Logdro Bangsaku by Blacius Subono” basically aims to examine the musical elements in the composition of Gamelan Logdro Bangsaku. The problems contained in this study include: 1. How is the process of creativity of B. Subono in creating the composition of Gamelan Logdro Bangsaku, 2. How is the musical study in the composition of Gamelan Logdro Bangsaku. The type of research used is qualitative research with data collection techniques including interviews, transcriptions, observations and literature studies. After going through the analysis process, the following conclusions and findings were found. First, the creation of Gamelan Logdro's composition was formed from the manifestation of B. Subono's artistic journey. Secondly, the creation of the composition of Gamelan Logdro Bangsaku also created a new interval of composing slendro and pelog tones sequentially with araka intervals that are not too far away. Third, the melody of the clash of notes that focuses on the beauty of the song's sentences. Fourth, there is a lot of musicality in the compositional work of Gamelan Lodgro Bangsaku.